Can rheometer be used for determination of baking stability of cocoa based filling creams - Aktar, Burcu Utku; Ishak, Arzu Karakas; Ozmen, Duygu; Agirbas, Halide Ezgi Tuna; Atil, Ozer; Toker, Omer Said (ELSEVIER SCI LTD, 2025)
Bake stable filling creams are important for some products such as biscuits, cakes, cookies, etc. In the present study, a rheometer-based method for determining the baking stability of the cream fillings was developed considering the consistency and fluidity of the fillings after baking. For this aim, the heating and cooling process was simulated depending on the temperature of the filling reached during the baking process of cookies. Three bake-stable and three bake-unstable filling creams were obtained from the market. Rheological, textural, and baking stability analysis were performed on the samples. Change in the apparent viscosity values of the samples was observed at temperature values from 20 degrees C to 105 degrees C and from 105 degrees C to 30 degrees C using rheometer. The percentage of viscosity change at 30 degrees C before and after the heating process was calculated. This value for stable samples was 67%, 73% and 9%. Fluctuation observation during the measurement is also important for stability. Unstable fillings have many fluctuations in the temperature versus apparent viscosity curve as their viscosity change value was lower. The absence of fluctuations on the temperature versus viscosity graph indicates the stability of the filling creams. The findings of the study indicated that a rheometer can be used as an effective tool for determining the baking stability of the creams with minimal effort, labor, sample requirement, and time.
Keywords: Chocolate; Rheology; Temperature sweep; Confectionery; Filling cream; FOOD; Engineering; Food Science & Technology